A New Approach to Designing the S-Shaped Annular Duct for Industrial Centrifugal Compressor - Ivan Yurko; German Bondarenko (International Journal of Rotating Machinery)
The authors propose an analytical method for designing the inlet annular duct for an industrial centrifugal compressor using high-order Bezier curves. Using the design of experiments (DOE) theory, the three-level full factorial design was developed for determination of influence of the dimensionless geometric parameters on the output criteria. Numerical research was carried out for determination of pressure loss coefficients and velocity swirl angles using the software system ANSYS CFX. Optimal values of the slope for a wide range of geometric parameters, allowing minimizing losses in the duct, have been found. The study has used modern computational fluid dynamics techniques to develop a generalized technique for future development of efficient variable inlet guide vane systems. Recommendations for design of the s-shaped annular duct for industrial centrifugal compressor have been given.